2023
DOI: 10.2174/0929867330666230111125141
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA: An Important Regulator of Atherosclerosis

Abstract: Long non-coding RNA (lncRNA) is a kind of biomolecule that can regulate important life activities such as cell proliferation, apoptosis, differentiation, aging, and body development. It has been found that lncRNAs are closely related to various diseases. In cardiovascular diseases, lncRNAs affect the expression level of related genes in atherosclerotic plaques, which are closely related to endothelial dysfunction, smooth muscle cell proliferation, macrophage dysfunction, abnormal lipid metabolism, and cellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…lncRNAs coordinate and integrate a variety of signaling pathways and play important roles in development, differentiation and disease ( Navarro et al, 2020 ). lncRNAs affect the expression levels of genes closely related to endothelial dysfunction, smooth muscle cell proliferation, macrophage dysfunction, abnormal lipid metabolism and cellular autophagy in atherosclerotic plaques, and thus are involved in regulating the onset and progression of atherogenesis ( Ma et al, 2023 ). For example, the long non-coding RNA HOXC-AS1 inhibits oxidized low-density lipoprotein (ox-LDL)-induced cholesterol accumulation by promoting the expression of HOXC6 in THP-1 macrophages ( Huang et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…lncRNAs coordinate and integrate a variety of signaling pathways and play important roles in development, differentiation and disease ( Navarro et al, 2020 ). lncRNAs affect the expression levels of genes closely related to endothelial dysfunction, smooth muscle cell proliferation, macrophage dysfunction, abnormal lipid metabolism and cellular autophagy in atherosclerotic plaques, and thus are involved in regulating the onset and progression of atherogenesis ( Ma et al, 2023 ). For example, the long non-coding RNA HOXC-AS1 inhibits oxidized low-density lipoprotein (ox-LDL)-induced cholesterol accumulation by promoting the expression of HOXC6 in THP-1 macrophages ( Huang et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ever-evolving high-throughput RNA sequencing technologies have allowed researchers to identify dysregulated lncRNAs in HF, both in animal models and in humans [ 29 , 30 ]. All of these findings propose that lncRNAs play an explicative role in the pathogenesis of, and may pose as a potential therapeutic target, for this life-threatening condition [ 31 , 32 ]. One of the remarkable aspects of the lncRNA–HF connection is the diversity of regulatory mechanisms involved [ 22 , 33 ]; for example, the lncRNA H19 has been shown to promote myocardial fibrosis by influencing the deposition of extracellular matrix components in the heart.…”
Section: Exploring the Connection Between Lncrna And Heart Failurementioning
confidence: 99%
“…Survivin is an apoptosis inhibitor gene with strong effect found at present. The gene is located on chromosome 17q25, and the expressed product consists of 142 amino acid residues with a relative molecular weight of 16.5 KD [4] containing 4 exons and 3 introns. At present, 8 members of the human IAP family have been discovered, including NAIP (BIRC1), c-IAP1 (BIRC2), cIAP2 (BIRC3), XIAP (BIRC4), Survivin (BIRC5), Apollon (BIRC6), and Livin (BIRC7) [5].…”
Section: Survivin Composition Structure Distribution and Localizationmentioning
confidence: 99%
“…At the beginning of mitosis, Survivin specifically binds to the spindle tubulin, which interferes with the normal progress of mitosis. Kobayashi et al found that Survivin is expressed in all tissues with cell proliferation, and Survivin is regularly and widely expressed in embryonic tissues, participating in cell growth and differentiation [4]. The expression of Survivin in normal tissues significantly increases during the G2/M phase, thereby protecting the normal progression of mitosis.…”
Section: Participate In Cell Division and Proliferationmentioning
confidence: 99%